Action oriented gender and innovation studies : reflections on methodology in the intersection of action research, feminist studies and technology studies - Nyberg, Ann-Christin (Luleå tekniska universitet, Arbetsvetenskap, 2009)
This paper discusses the possibility to fruitfully combine methodological perspectives on change from action research, feminist studies, and technology studies/engineering in the study of gender and innovation. The perspectives on change are discussed in relation to practical experiences from the research project ‘Gender Equality for Sustainable Growth', which is a study of gender equality and work for change within twelve innovation systems. The research project explores how gender equality policy is implemented in industrial practise via interviews and document studies. The methodology of the project is action oriented in the sense that it aims not only at analyzing how gender equality policy is implemented but also to support the utilization of gender both as a tool of analysis and a tool of change within the studied innovation systems. The project is carried out in interaction with the Vinnväxt innovation system's management groups, the Swedish Agency for Innovation Systems Vinnova and the Division of Gender and Innovation at Luleå University of Technology. The focus on change adds an experimental dimension to the project which is related to the simultaneous doing of gender and technology. Godkänd; 2009; 20091215 (annnyb)